Kanayatn Dayak Beliefs about Jubata in the Perspective of the Divine Philosophy - Laurentius Prasetyo; Kristianus Kristianus; Magdalena Magdalena (International Journal of Multi Discipline Science, 2023)
This research was motivated by the very diverse understanding of the Dayak people about Jubata. The purpose of this research was to find the concept of Jubata that fits the beliefs of the Dayak people outside the influence of Catholicism. The research method was qualitatively descriptive with an ethnographic approach. The research team was the key research instrument, where the research subjects were customary stakeholders and traditional practitioners who are in the research location. Data collection techniques by interviewing research subjects. Data analysis was carried out by codifying and grouping data based on the answers to the interviews conducted. The grouping results were then interpreted and then discussed again with the leaders in the form of a Focus Group Discussion. Thus the concept obtained was a joint conclusion of the parties involved in the research. The results showed that Jubata, which is believed by the Kanayatn Dayak people, is everywhere. Jubata lives close to human life, such as in homes, ritual areas (usually indicated by the sound of the keto bird), farming areas, gardens, settlements and in areas where people are active. The concept of Jubata is heavily influenced by the Hindu belief that there are many Gods, while Catholics believe in one God. Academically, the results of this study can be used as a reference for dialectics related to the Kanayatn Dayak Belief System. The Research Team has succeeded in uncovering the concept of Jubata which is believed by the Kanayatn Dayak people who tend to be Syncretistic. Dayak people believe in God according to their religion but also believe in Jubata according to the beliefs of their ancestors. Jubata is pragmatically the same as God but spiritually Jubata is different from God. Ambiguity regarding this occurs because the religion adopted is different from the belief system that is believed. The Kanayatn Dayak people are indeed at a crossroads, whether to Heaven or Subayatn.